Monoamine structure and its effect on fully reacted substructures to synergistically toughen epoxy amine networks via topological control - Nguyen Thao Phan; Houlei Gan; David Szmalko; Claudia Creighton; Cara M. Doherty; Durga Acharya; Daniel J. Eyckens; Russell J. Varley (Chemical Engineering Journal, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

The brain network underlying social participation: a multimodal, data-driven investigation - Mia G. Casburn; Aodán Laighneach; Evie Doherty; Fergus Quilligan; Andrea Fernandes; Emma Corley; Gary Donohoe; Pilib Ó Broin; Derek W. Morris; Dara M. Cannon (Brain Imaging and Behavior, 2026)
Identifying brain phenotypes influencing social participation may help understand social deficits in psychiatric disorders. Previous research shows methodological inconsistencies, lacking consensus on which brain regions are crucial. Data-driven variable selection may overcome this, facilitating unbiased replication and discovery of social brain regions. We compare data-driven selection to literature-identification of brain regions in explaining social participation variation. In 37,576 UK Biobank participants (mean age 65 ± 8, 53% female) with structural and functional neuroimaging data, social participation (range 0–10) was derived by combining leisure activity participation and friend/family visits. First, literature review identified a subset of brain regions previously associated with social measures. Secondly, recursive feature elimination selected a subset of imaging-derived phenotypes in 25% ( n = 9,394) of the sample. Hierarchical regression in the remaining 75% ( n = 28,152) compared whether data-selected or literature-identified brain phenotype-sets explained more variance in social participation. Individual p-values were corrected for multiple comparisons using the false discovery rate. Recursive feature elimination selected 198 imaging-derived phenotypes. Data-selected imaging-derived-phenotypes explained more variance in social participation (1.31%) than literature-identified (0.84%, F = 3.17, p < 0.0001). Seventeen imaging-derived-phenotypes were associated with social participation including mid-posterior-cingulate, inferior-frontal/orbital and insular thickness, and functional connectivity between pericentral with medial frontoparietal and cerebellar networks. Multi-modal brain imaging-derived phenotypes can predict small but significant variation in social participation. We confirmed previously identified social brain associations of pericentral and medial frontoparietal, and orbital regions while also implicating novel relationships with the insula, acoustic radiation, and lateral frontoparietal networks. This highlights the value of data-driven approaches in solidifying social brain regional involvement, outperforming literature-based methods, and revealing previously undetected relationships.

Influence of feed ingredient preservation method and protein source inclusion on performance, nutrient digestibility, and environmental impacts of finishing pigs - Shane Maher; Nicholas M. Holden; Torres Sweeney; Kathryn R. Connolly; John V. O’Doherty (Animal Feed Science and Technology, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Plant’s developmental decision to either abort a flower or set seed - Dinesh Kumar Saini; Juliana M. Espíndola Lima; Ramanjulu Sunkar; Colleen Doherty; Krishna S.V. Jagadish (Trends in Plant Science, 2026)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

Transcriptomic analysis reveals time-of-day-specific genes and gene regulatory networks in response to chilling stress in sorghum - Kanjana Laosuntisuk; Amaranatha Vennapusa; Impa M. Somayanda; S. V. Krishna Jagadish; Colleen J. Doherty (Plant Physiology Reports, 2025)
Sorghum is a versatile crop with many uses, ranging from human consumption to biofuel production. In the U.S., sorghum experiences heat stress during flowering in the summer. Several strategies have been developed to reduce yield loss caused by heat stress. One of the most reliable strategies is ‘heat escape’, in which early-season planting shifts the crop’s reproductive phase to occur before heat stress exposure. However, this heat escape strategy is limited due to sorghum’s sensitivity to early-season chilling. In sorghum, early-season chilling stress negatively affects seed germination, emergence, and seedling vigor. Candidate chilling-tolerant genes in sorghum have been proposed, but the molecular mechanisms of the candidate genes in chilling stress response have not been well established. We hypothesized that many transcriptional responses critical for sorghum’s response to low temperature have been missed by not examining gene expression at multiple times throughout the day. Here, we investigated the effect of chilling stress and time of day on transcriptional responses using 3′ RNA-Seq. We found that time-of-day gated gene expression in response to chilling stress results in various transcriptional response patterns, each with unique biological processes. Weighted gene correlation network analysis (WGCNA) identified modules of transcripts that are specifically responsive to nighttime chilling. Candidate regulatory transcription factors (TFs) of the chilling stress response in sorghum were identified through gene regulatory network analysis. Our results demonstrate that the time of day samples are collected substantially affects our understanding of chilling tolerance, and suggest that a full capture of the network of chilling stress responses requires an examination of multiple times of day. By profiling transcription across different times of day under chilling conditions, we identify regulatory programs that can be leveraged to expand early-planting windows.

Analysis of blood-based DNA methylation signatures of aging and disease progression in inflammatory bowel disease - Trevor Doherty; Edel McDermott; Sarah Jane Delany; Hugh Mulcahy; Therese M. Murphy (Human Genetics, 2025)
Inflammatory bowel diseases (IBDs) are chronic inflammatory disorders influenced by environmental factors and characterised by a dysregulated immune response. DNA methylation (DNAm) a key epigenetic mechanism plays a role in the etiology of complex diseases like IBD. Epigenetic clocks which estimate biological aging through DNAm patterns have also been linked to various health states, including IBD. Previously, we profiled DNA methylation in peripheral blood from adult IBD patients and controls using the Illumina 450K microarray ( n = 184). We now expand this dataset with 8-year clinical follow-up data, including disease progression and treatment response. Additionally, we generate second and third-generation epigenetic clock measures in this cohort to investigate if IBD patients exhibit epigenetic age acceleration compared to healthy controls. We identified one CpG site (cg03583111) significantly differentially methylated in IBD patients with long-term clinical recurrence (after the first year of study) compared to non-recurrence (no treatment escalation after 8 years). We assessed DNAm aging signatures in IBD patients versus controls, finding evidence of significant epigenetic age acceleration, as measured by three epigenetic clocks (GrimAge, GrimAge2, and DunedinPACE), in IBD patients compared to controls. These associations were replicated in two independent IBD cohorts: adult (GSE87648, n = 377) and paediatric (GSE112611, n = 238). Moreover, we observed higher age acceleration (GrimAge, U = 669, p = 0.003) and a faster pace of aging (DunedinPACE, t = 3.233, p = 0.002) in patients with active UC compared to inactive disease, but not for CD. These findings suggest that blood-based DNAm signatures could serve as biomarkers for detecting, monitoring, and classifying IBD.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

Structure and composition of yellowtail kingfish ( Seriola lalandi ) otoliths: implications for using aquaculture‐reared fish to reconstruct life histories - Belinda K. Goddard; Laura M. Otter; Julian M. Hughes; Fabrice R. A. Jaine; Jasmin C. Martino; Ulrike Troitzsch; Jackson Doherty; Hayden T. Schilling (Journal of Fish Biology, 2025)
Understanding fish life history is essential for effective management of fisheries, but continuous tracking over lifetime temporal scales can be difficult. Fish otoliths contain a natural biogeochemical record of ambient environmental conditions and habitat use over such scales. However, ecological interpretations of these elemental compositions can be influenced by the structural composition of calcium carbonate otoliths, which can vary between wild and aquaculture fish as well as across species. As such, we used in situ confocal micro‐Raman spectroscopy and powder X‐ray diffraction to assess and quantify, respectively, the calcium carbonate polymorphs of the otoliths of aquaculture and wild yellowtail kingfish ( Seriola lalandi ) to validate whether the otoliths from aquaculture fish can be used to interpret patterns seen in the otoliths of wild fish. We then analysed major and minor trace elements using wavelength dispersive X‐ray spectroscopy to investigate the potential habitat use of wild S. lalandi . The elemental composition of S. lalandi otoliths was examined across three cross‐sectioned growth zones: the first (i.e. oldest) annulus (growth ring), the outermost (i.e. most recent) annulus and mid‐way between these. All otoliths were shown to be composed of aragonite, with the exception of small proportions (0.5 wt%) of vaterite in a single wild S. lalandi otolith. This finding indicates that otoliths of aquaculture S. lalandi , reared in known conditions, are appropriate to interpret stable isotope analyses in wild S. lalandi . Wild‐caught S. lalandi otoliths had concentrations of barium and manganese below detectable limits ( S. lalandi were not in estuarine or brackish environments when the analysed annuli were formed, suggesting these environments are not used for spawning.

Numerical Analysis of Triaxial Tests for Interpreting Sample Stiffness with Existing Measurement Systems - W. Du; B. M. Lehane; J. P. Doherty; Z. Wang (Geotechnical and Geological Engineering, 2025)
This paper presents the first systematic numerical study employing a realistic elasto-plastic non-linear soil model to examine factors affecting the measurement of soil stiffness at low to intermediate strains in the triaxial apparatus. The study is motivated by the development of new image-based measurement techniques for triaxial testing. The results from numerical simulations are presented that quantify the influence on sample stiffness determination of three important features common to all triaxial tests, namely: the misalignment of the loading direction and the top of the sample (and indirectly bedding errors), the use of fixed or free load cell connections and the effect of system compliance. The analyses compare data obtained using four different instrumentation systems employed for axial strain measurement with overall predicted deformations and elemental response of a typical sand sample. The paper highlights some of the significant errors that can occur in standard triaxial tests and makes recommendations to assist more accurate determinations of sample stiffness. It is also shown numerically that, despite sample and test imperfections, the common approach of averaging data from at least two strain gauges located on a triaxial sample’s middle third can lead to reasonable inference of a soil’s elemental Youngs modulus.

Characterising neonicotinoid insecticide exposures among the Irish population using human biomonitoring - Sonja A. Wrobel; Darragh M. Doherty; Holger M. Koch; Heiko U. Käfferlein; Daniel Bury; Craig Slattery; Marie A. Coggins; Alison Connolly (International Journal of Hygiene and Environmental Health, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Field measurements of steelhead trout Oncorhynchus mykiss distribution, swimming behavior and response to water current exposure in a sea cage - M. Chambers; M. Doherty; M. Coogan; C. Rillahan; J. DeCew; P. Lader; W.H. Howell (Aquaculture, 2025)

Ten questions concerning the future of residential indoor air quality and its environmental justice implications - D. Booker; G. Petrou; L. Chatzidiakou; D. Das; F. Farooq; L. Ferguson; OE.I. Jutila; K. Milczewska; M. Modlich; A. Moreno-Rangel; S.K. Thakrar; A.M. Yeoman; et al. (Building and Environment, 2025)

Examining factors influencing varietal resistance to Rhyzopertha dominica (F.) in stored rice - Ethan M. Doherty; Nohelys Camano-Flores; Qian Sun; Blake E. Wilson (Crop Protection, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

‘Megafire’—You May Not Like It, But You Cannot Avoid It - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2025)
Aim The term ‘megafire’ is increasingly used to describe large fires worldwide. We proposed a size‐based definition of megafire—fires exceeding 10,000 ha arising from single or multiple related ignition events. A recent perspective in Global Ecology and Biogeography argues against a size‐based definition of megafire and suggest that the term is too emotive for scientific use. We highlight that many scientific terms originate from common terms. These terms are often defined once they enter the scientific lexicon, enhancing both scientific understanding and public communication. We argue that standardised definitions facilitate better prediction, preparation, and management of fire events. Location Worldwide. Time Period 2022–2023. Methods We conducted an updated structured review of the term ‘megafire’ and its use and definition in the peer‐reviewed scientific literature, collating definitions and descriptions and identifying the criteria frequently invoked to define the term. Results We demonstrate an increase in the use of ‘megafire’ in the scientific literature since our original definition in 2022, with many studies adopting the > 10,000 ha size‐based criterion. Main Conclusions We contend that abandoning the term is neither practical, possible, nor beneficial. Instead, consistent usage underpinned by clear definitions is essential. Adopting a clear, size‐based definition of megafire strengthens clarity and comparability across research and management practices globally. Precision in terminology is crucial for advancing research, improving communication, and informing effective fire management and policy.

Pharmacodynamic characterization and evaluation of oxidative stress effects of digitoxigenin derivatives on HeLa cells - Jessica M. M. Valadares; Pedro Azalim-Neto; Xiaofan Liu; Nathallia Cavalcanti Carrozza; George A. O’Doherty; Luis Eduardo M. Quintas; Leandro A. Barbosa (The Journal of Membrane Biology, 2025)

Environmental and ecological factors associated with stinging jellyfish at a tourism hotspot in the Gulf of Thailand - Rahul Mehrotra; Pasicha Chaikaew; Elouise Haskin; Kirsty Magson; Chad M. Scott; Ruth Doherty (Estuarine, Coastal and Shelf Science, 2024)

Animal-borne sensors reveal high human impact on soundscapes near a critical sea turtle nesting beach - Francesco Garzon; Pierre Didier Agamboue; Jack A. Boyle; Philip D. Doherty; Angela Formia; Brendan J. Godley; Lucy A. Hawkes; David A. Mann; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Guy-Phillipe Sounguet; et al. (Biological Conservation, 2024)

Ticks and lyme disease in natural areas: A segmentation analysis of visitor perceptions of risk and preferred communication strategies - Ryan M. Brady; Christopher J. Lemieux; Sean T. Doherty (Journal of Outdoor Recreation and Tourism, 2024)

Integrating Shared Socioeconomic Pathway-informed adaptation into temperature-related mortality projections under climate change - Kai Wan; Shakoor Hajat; Ruth M. Doherty; Zhiqiang Feng (Environmental Research, 2024)

Maternal PFOS exposure affects offspring development in Nrf2-dependent and independent ways in zebrafish (Danio rerio) - Marjorie Marin; Kate M. Annunziato; Madeline C. Tompach; Wenle Liang; Sarah M. Zahn; Sida Li; Jeffery Doherty; Jonghwa Lee; John M. Clark; Yeonhwa Park; Alicia R. Timme-Laragy (Aquatic Toxicology, 2024)

Experimentally testing animal responses to prescribed fire size and severity - Tim S. Doherty; Daniel F. Bohórquez Fandiño; Darcy J. Watchorn; Sarah M. Legge; Chris R. Dickman (Conservation Biology, 2024)
Deserts are often highly biodiverse and provide important habitats for many threatened species. Fire is a dominant disturbance in deserts, and prescribed burning is increasingly being used by conservation managers and Indigenous peoples to mitigate the damaging effects of climate change, invasive plants, and land‐use change. The size, severity, and patchiness of fires can affect how animals respond to fire. However, there are almost no studies examining such burn characteristics in desert environments, which precludes the use of such information in conservation planning. Using a before‐after control‐impact approach with 20 sampling sites, we studied the outcomes of 10 prescribed burns of varying size (5–267 ha), severity, and patchiness to identify which variables best predicted changes in small mammal and reptile species richness and abundance. Three of the 13 species showed a clear response to fire. Captures increased for 2 species (1 mammal, 1 reptile) and decreased for 1 species (a reptile) as the proportional area burned around traps increased. Two other mammal species showed weaker positive responses to fire. Total burn size and burn patchiness were not influential predictors for any species. Changes in capture rates occurred only at sites with the largest and most severe burns. No fire‐related changes in capture rates were observed where fires were small and very patchy. Our results suggest that there may be thresholds of fire size or fire severity that trigger responses to fire, which has consequences for management programs underpinned by the patch mosaic burning paradigm. The prescribed burns we studied, which are typical in scale and intensity across many desert regions, facilitated the presence of some taxa and are unlikely to have widespread or persistent negative impacts on small mammal or reptile communities in this ecosystem provided that long unburned habitat harboring threatened species is protected.

Accuracy of patient race and ethnicity data in a central cancer registry - Rachel R. Codden; Carol Sweeney; Blessing S. Ofori-Atta; Kimberly A. Herget; Kacey Wigren; Sandra Edwards; Marjorie E. Carter; Rachel D. McCarty; Mia Hashibe; Jennifer A. Doherty; Morgan M. Millar (Cancer Causes & Control, 2024)

A nose for trouble: ecotoxicological implications for climate change and disease in Saiga antelope (S. t. tatarica) - S. T. Mullineaux; J. M. McKinley; N. J. Marks; R. Doherty; D. M. Scantlebury (Environmental Geochemistry and Health, 2024)
In recent decades, Saiga antelope ( Saiga t. tatarica ) mass die-offs have become more common. The mass die-off of 2015 in central Kazakhstan, recorded 140,000 individual deaths across multiple herds. Previously, research has shown atmospheric humidity, the bacterium Pasteurella multocida serotype B, and resultant haemorrhagic septicaemia, were the primary cause. However, other synergistic factors may have impacted this process. Here we use a multivariate compositional data analysis (CoDA) approach to assess what other factors may have been involved. We show a pollutant linkage mechanism where relative humidity and dewpoint temperature combine with environmental pollutants, potentially toxic elements (e.g., Hg, As), complex carbon compounds (e.g., Acetone, Toluene), and inorganic compounds (e.g., CHx, SO 2 ) which affected the Saiga during the calving season (start and peak) and at the onset of the mass die-off. We suggest a mechanism for this process. Upon arrival at their carving grounds, the Saiga experienced a sudden precipitation event, a spike in temperatures, and resultant high humidity occurs. The infectious bacterium P . multocida serotype B then spreads. Further, environmental pollutants contained within steppe soils are released to the air, forming localised smog events, these synergistically combine, and mass die-off occurs.

Photocatalytic Degradation of Dyes in Wastewater Using Solar Enhanced Nickel Oxide (NiO) Nanocatalysts Prepared by Chemical Methods - Abolanle S. Adekunle; John A. O. Oyekunle; Solomon S. Durodola; Lateefat M. Durosinmi; Winston O. Doherty; Mustapha O. Olayiwola; Bolaji C. Adegboyega; Temitope A. Ajayeoba; Olawale F. Akinyele; Oluwatobi S. Oluwafemi (Journal of Fluorescence, 2023)

Using coral holes to explore the historical ecology of Guam’s coral reefs - Jonathan D. Cybulski; John M. Doherty; Carly LaRoche; Kelly Donovan Gutkowski; Zizhan Luo; Elizabeth J. Malloy; Laurel MacMillan; Laurie Raymundo; Kiho Kim (Coral Reefs, 2023)

A methodology to calibrate the PICSI cyclic p-y model using experimental results and optimisation - M. Guevara; J.P. Doherty; P.G. Watson; D.J. White (Ocean Engineering, 2023)

Placental BCRP transporter reduces cadmium accumulation and toxicity in immortalized human trophoblasts - Ranran Zhang; Lauren Walker; Xia Wen; Cathleen Doherty; Ludwik Gorczyca; Brian Buckley; Emily S. Barrett; Lauren M. Aleksunes (Reproductive Toxicology, 2023)

P16-33: Identifying and characterizing toxicity liabilities of pharmaceuticals using ToxProfiler: A blinded case study with the ITLF consortium - B. Ter Braak; L. Wolters; K. Elbertse; M. Beilmann; H. Boonen; A. Doherty; F. Van Goethem; P. Hewitt; J. Hornberg; J. Koch; S. Kusterman; J. Lyon; et al. (Toxicology Letters, 2023)

Cadmium reduces growth of male fetuses by impairing development of the placental vasculature and reducing expression of nutrient transporters - Danielle Kozlosky; Alexander Lu; Cathleen Doherty; Brian Buckley; Michael J. Goedken; Richard K. Miller; Emily S. Barrett; Lauren M. Aleksunes (Toxicology and Applied Pharmacology, 2023)

Protective role of the placental efflux transporter BCRP/ABCG2 in the relationship between prenatal cadmium exposure, placenta weight, and size at birth - Emily S. Barrett; Zorimar Rivera-Núñez; Kylie Getz; Pamela Ohman-Strickland; Ranran Zhang; Danielle Kozlosky; Cathleen L. Doherty; Brian T. Buckley; Jessica Brunner; Richard K. Miller; Thomas G. O'Connor; Lauren M. Aleksunes (Environmental Research, 2023)

Stored rice varietal resistance towards Sitophilus oryzae - Ethan M. Doherty; Qian Sun; Blake E. Wilson (Crop Protection, 2023)

Historical trend of ozone-depleting substances and hydrofluorocarbon concentrations during 2004–2020 derived from satellite observations and estimates for global emissions - Ao Chen; Di Chen; Xiaoyi Hu; Christina M. Harth; Dickon Young; Jens Mühle; Paul B. Krummel; Simon O'Doherty; Ray F. Weiss; Ronald G. Prinn; Xuekun Fang (Environmental Pollution, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

Resetting our expectations for parasites and their effects on species interactions: a meta‐analysis - Adam Z. Hasik; Daniela de Angeli Dutra; Jean‐François Doherty; Meghan A. Duffy; Robert Poulin; Adam M. Siepielski (Ecology Letters, 2023)
Despite the ubiquitous nature of parasitism, how parasitism alters the outcome of host–species interactions such as competition, mutualism and predation remains unknown. Using a phylogenetically informed meta‐analysis of 154 studies, we examined how the mean and variance in the outcomes of species interactions differed between parasitized and non‐parasitized hosts. Overall, parasitism did not significantly affect the mean or variance of host–species interaction outcomes, nor did the shared evolutionary histories of hosts and parasites have an effect. Instead, there was considerable variation in outcomes, ranging from strongly detrimental to strongly beneficial for infected hosts. Trophically‐transmitted parasites increased the negative effects of predation, parasites increased and decreased the negative effects of interspecific competition for parasitized and non‐parasitized heterospecifics, respectively, and parasites had particularly strong negative effects on host species interactions in freshwater and marine habitats, yet were beneficial in terrestrial environments. Our results illuminate the diverse ways in which parasites modify critical linkages in ecological networks, implying that whether the cumulative effects of parasitism are considered detrimental depends not only on the interactions between hosts and their parasites but also on the many other interactions that hosts experience.

What do you mean, ‘megafire’? - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.

Microbiome assembly in thawing permafrost and its feedbacks to climate - Jessica G. Ernakovich; Robyn A. Barbato; Virginia I. Rich; Christina Schädel; Rebecca E. Hewitt; Stacey J. Doherty; Emily D. Whalen; Benjamin W. Abbott; Jiri Barta; Christina Biasi; Chris L. Chabot; Jenni Hultman; et al. (Global Change Biology, 2022)
The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost–climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post‐thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to climate change. Based on our review of the Arctic microbiome, permafrost microbiology, and community ecology, we propose that Assembly Theory provides a framework to better understand thaw‐mediated microbiome changes and the implications for community function and climate feedbacks. This framework posits that the prevalence of deterministic or stochastic processes indicates whether the community is well‐suited to thrive in changing environmental conditions. We predict that on a short timescale and following high‐disturbance thaw (e.g., thermokarst), stochasticity dominates post‐thaw microbiome assembly, suggesting that functional predictions will be aided by detailed information about the microbiome. At a longer timescale and lower‐intensity disturbance (e.g., active layer deepening), deterministic processes likely dominate, making environmental parameters sufficient for predicting function. We propose that the contribution of stochastic and deterministic processes to post‐thaw microbiome assembly depends on the characteristics of the thaw disturbance, as well as characteristics of the microbial community, such as the ecological and phylogenetic breadth of functional guilds, their functional redundancy, and biotic interactions. These propagate across space and time, potentially providing a means for predicting the microbial forcing of greenhouse gas feedbacks to global climate change.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Animal mortality during fire - Chris J. Jolly; Chris R. Dickman; Tim S. Doherty; Lily M. van Eeden; William L. Geary; Sarah M. Legge; John C. Z. Woinarski; Dale G. Nimmo (Global Change Biology, 2022)
Earth's rapidly warming climate is propelling us towards an increasingly fire‐prone future. Currently, knowledge of the extent and characteristics of animal mortality rates during fire remains rudimentary, hindering our ability to predict how animal populations may be impacted in the future. To address this knowledge gap, we conducted a global systematic review of the direct effects of fire on animal mortality rates, based on studies that unequivocally determined the fate of animals during fire. From 31 studies spanning 1984–2020, we extracted data on the direct impacts of fire on the mortality of 31 species from 23 families. From these studies, there were 43 instances where direct effects were measured by reporting animal survival from pre‐ to post‐fire. Most studies were conducted in North America (52%) and Oceania (42%), focused largely on mammals (53%) and reptiles (30%), and reported mostly on animal survival in planned (82%) and/or low severity (70%) fires. We found no studies from Asia, Europe or South America. Although there were insufficient data to conduct a formal meta‐analysis, we tested the effect of fire type, fire severity, fire regime, animal body mass, ecological attributes and class on survival. Only fire severity affected animal mortality, with a higher proportion of animals being killed by high than low severity fires. Recent catastrophic fires across the globe have drawn attention to the plight of animals exposed to wildfire. Yet, our systematic review suggests that a relatively low proportion of animals (mean predicted mortality [95% CI] = 3% [1%–9%]) are killed during fire. However, our review also underscores how little we currently know about the direct effects of fire on animal mortality, and highlights the critical need to understand the effects of high severity fire on animal populations.

Evaluation of sex-based differences in airway size and the physiological implications - Leah M. Mann; Sarah A. Angus; Connor J. Doherty; Paolo B. Dominelli (European Journal of Applied Physiology, 2021)

Chronic kidney disease of unknown origin is associated with environmental urbanisation in Belfast, UK - Jennifer M. McKinley; Ute Mueller; Peter M. Atkinson; Ulrich Ofterdinger; Siobhan F. Cox; Rory Doherty; Damian Fogarty; J. J. Egozcue; V. Pawlowsky-Glahn (Environmental Geochemistry and Health, 2021)
Chronic kidney disease (CKD), a collective term for many causes of progressive renal failure, is increasing worldwide due to ageing, obesity and diabetes. However, these factors cannot explain the many environmental clusters of renal disease that are known to occur globally. This study uses data from the UK Renal Registry (UKRR) including CKD of uncertain aetiology (CKDu) to investigate environmental factors in Belfast, UK. Urbanisation has been reported to have an increasing impact on soils. Using an urban soil geochemistry database of elemental concentrations of potentially toxic elements (PTEs), we investigated the association of the standardised incidence rates (SIRs) of both CKD and CKD of uncertain aetiology (CKDu) with environmental factors (PTEs), controlling for social deprivation. A compositional data analysis approach was used through balances (a special class of log contrasts) to identify elemental balances associated with CKDu. A statistically significant relationship was observed between CKD with the social deprivation measures of employment, income and education (significance levels of 0.001, 0.01 and 0.001, respectively), which have been used as a proxy for socio-economic factors such as smoking. Using three alternative regression methods (linear, generalised linear and Tweedie models), the elemental balances of Cr/Ni and As/Mo were found to produce the largest correlation with CKDu. Geogenic and atmospheric pollution deposition, traffic and brake wear emissions have been cited as sources for these PTEs which have been linked to kidney damage. This research, thus, sheds light on the increasing global burden of CKD and, in particular, the environmental and anthropogenic factors that may be linked to CKDu, particularly environmental PTEs linked to urbanisation.

Multiple-endpoint in vitro carcinogenicity test in human cell line TK6 distinguishes carcinogens from non-carcinogens and highlights mechanisms of action - Katherine E. Chapman; Eleanor C. Wilde; Fiona M. Chapman; Jatin R. Verma; Ume-Kulsoom Shah; Leanne M. Stannard; Anna L. Seager; James A. Tonkin; M. Rowan Brown; Ann T. Doherty; George E. Johnson; Shareen H. Doak; et al. (Archives of Toxicology, 2021)
Current in vitro genotoxicity tests can produce misleading positive results, indicating an inability to effectively predict a compound’s subsequent carcinogenic potential in vivo. Such oversensitivity can incur unnecessary in vivo tests to further investigate positive in vitro results, supporting the need to improve in vitro tests to better inform risk assessment. It is increasingly acknowledged that more informative in vitro tests using multiple endpoints may support the correct identification of carcinogenic potential. The present study, therefore, employed a holistic, multiple-endpoint approach using low doses of selected carcinogens and non-carcinogens (0.001–770 µM) to assess whether these chemicals caused perturbations in molecular and cellular endpoints relating to the Hallmarks of Cancer. Endpoints included micronucleus induction, alterations in gene expression, cell cycle dynamics, cell morphology and bioenergetics in the human lymphoblastoid cell line TK6. Carcinogens ochratoxin A and oestradiol produced greater Integrated Signature of Carcinogenicity scores for the combined endpoints than the “misleading” in vitro positive compounds, quercetin, 2,4-dichlorophenol and quinacrine dihydrochloride and toxic non-carcinogens, caffeine, cycloheximide and phenformin HCl. This study provides compelling evidence that carcinogens can successfully be distinguished from non-carcinogens using a holistic in vitro test system. Avoidance of misleading in vitro outcomes could lead to the reduction and replacement of animals in carcinogenicity testing.

Assessing the Effects of Banana Pingers as a Bycatch Mitigation Device for Harbour Porpoises (Phocoena phocoena) - Lucy C. M. Omeyer; Philip D. Doherty; Sarah Dolman; Robert Enever; Allan Reese; Nicholas Tregenza; Ruth Williams; Brendan J. Godley (Frontiers in Marine Science, 2020)

Organophosphate Esters: Are These Flame Retardants and Plasticizers Affecting Children’s Health? - Brett T. Doherty; Stephanie C. Hammel; Julie L. Daniels; Heather M. Stapleton; Kate Hoffman (Current Environmental Health Reports, 2019)

Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Brittany T. Trew; Hedley S. Grantham; Christian Barrientos; Tim Collins; Philip D. Doherty; Angela Formia; Brendan J. Godley; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Dominic Tilley; Matthew J. Witt; et al. (Frontiers in Marine Science, 2019)

Multidisciplinary investigations of the diets of two post-medieval populations from London using stable isotopes and microdebris analysis - Madeleine Bleasdale; Paola Ponce; Anita Radini; Andrew S. Wilson; Sean Doherty; Patrick Daley; Chloe Brown; Luke Spindler; Lucy Sibun; Camilla Speller; Michelle M. Alexander (Archaeological and Anthropological Sciences, 2019)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Joint exposure to smoking, excessive weight, and physical inactivity and survival of ovarian cancer patients, evidence from the Ovarian Cancer Association Consortium - Albina N. Minlikeeva; Rikki Cannioto; Allan Jensen; Susanne K. Kjaer; Susan J. Jordan; Brenda Diergaarde; J. Brian Szender; Kunle Odunsi; Hani Almohanna; Paul Mayor; Kirsten Starbuck; Emese Zsiros; et al. (Cancer Causes & Control, 2019)

Connectivity-based characterisation of subcortical grey matter pathology in frontotemporal dementia and ALS: a multimodal neuroimaging study - Peter Bede; Taha Omer; Eoin Finegan; Rangariroyashe H. Chipika; Parameswaran M. Iyer; Mark A. Doherty; Alice Vajda; Niall Pender; Russell L. McLaughlin; Siobhan Hutchinson; Orla Hardiman (Brain Imaging and Behavior, 2018)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Correction to: Acute phenylalanine/tyrosine depletion of phasic dopamine in the rat brain - Tatiana A. Shnitko; Sarah C. Taylor; Sierra J. Stringfield; Shannon L. Zandy; Roberto U. Cofresí; James M. Doherty; William B. Lynch; Charlotte A. Boettiger; Rueben A. Gonzales; Donita L. Robinson (Psychopharmacology, 2018)

Cold Water in a Warm World: Investigating the Origin of the Nordic Seas' Unique Surface Properties During MIS 11 - John M. Doherty; Benoit Thibodeau (Frontiers in Marine Science, 2018)

Transformation of detritus by a European native and two invasive alien freshwater decapods - Thomas M. Doherty-Bone; Alison M. Dunn; Caroline Liddell; Lee E. Brown (Biological Invasions, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A novel, integrated in vitro carcinogenicity test to identify genotoxic and non-genotoxic carcinogens using human lymphoblastoid cells - Eleanor C. Wilde; Katherine E. Chapman; Leanne M. Stannard; Anna L. Seager; Katja Brüsehafer; Ume-Kulsoom Shah; James A. Tonkin; M. Rowan Brown; Jatin R. Verma; Ann T. Doherty; George E. Johnson; Shareen H. Doak; et al. (Archives of Toxicology, 2018)

Informing Marine Protected Area Designation and Management for Nesting Olive Ridley Sea Turtles Using Satellite Tracking - Tiffany M. Dawson; Angela Formia; Pierre D. Agamboué; Georges M. Asseko; François Boussamba; Floriane Cardiec; Emmanuel Chartrain; Philip D. Doherty; J. Michael Fay; Brendan J. Godley; Francis Lambert; Brice D. Koumba Mabert; et al. (Frontiers in Marine Science, 2017)

The essential Drosophila CLAMP protein differentially regulates non-coding roX RNAs in male and females - Jennifer A. Urban; Caroline A. Doherty; William T. Jordan; Jacob E. Bliss; Jessica Feng; Marcela M. Soruco; Leila E. Rieder; Maria A. Tsiarli; Erica N. Larschan (Chromosome Research, 2017)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

GPS Amplitude Scintillations over Kampala, Uganda, During 2010–2011 - Andrew O. Akala; Raphael Idolor; Florence M. D’Ujanga; Patricia H. Doherty (Acta Geophysica, 2016)

Adaptation services and pathways for the management of temperate montane forests under transformational climate change - Matthew J. Colloff; Michael D. Doherty; Sandra Lavorel; Michael Dunlop; Russell M. Wise; Suzanne M. Prober (Climatic Change, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Acute phenylalanine/tyrosine depletion of phasic dopamine in the rat brain - Tatiana A. Shnitko; Sarah C. Taylor; Sierra J. Stringfield; Shannon L. Zandy; Roberto U. Cofresí; James M. Doherty; William B. Lynch; Charlotte A. Boettiger; Rueben A. Gonzales; Donita L. Robinson (Psychopharmacology, 2016)

Attenuation of nicotine-taking and nicotine-seeking behavior by the mGlu2 receptor positive allosteric modulators AZD8418 and AZD8529 in rats - Xia Li; Manoranjan S. D’Souza; Ana M. Niño; James Doherty; Alan Cross; Athina Markou (Psychopharmacology, 2016)

Histopathological alterations, biochemical responses and acetylcholinesterase levels in Clarias gariepinus as biomarkers of exposure to organophosphates pesticides - V. F. Doherty; M. K. Ladipo; I. A. Aneyo; A. Adeola; W. Y. Odulele (Environmental Monitoring and Assessment, 2016)

Role of Emitter and Severity of Aggression Influence the Agonistic Vocalizations of Geoffroy’s Spider Monkeys (Ateles geoffroyi) - José D. Ordóñez-Gómez; Jacob C. Dunn; Víctor Arroyo-Rodríguez; María G. Méndez-Cárdenas; Alejandra Márquez-Arias; Ana M. Santillán-Doherty (International Journal of Primatology, 2015)

The Effects of Oxygen Transition on Community Respiration and Potential Chemoautotrophic Production in a Seasonally Stratified Anoxic Estuary - Dong Y. Lee; Michael S. Owens; Mary Doherty; Erin M. Eggleston; Ian Hewson; Byron C. Crump; Jeffrey C. Cornwell (Estuaries and Coasts, 2015)

STC1 expression is associated with tumor growth and metastasis in breast cancer - Andy C-M Chang; Judy Doherty; Lily I. Huschtscha; Richard Redvers; Christina Restall; Roger R. Reddel; Robin L. Anderson (Clinical & Experimental Metastasis, 2015)

Light-absorbing particles in snow and ice: Measurement and modeling of climatic and hydrological impact - Yun Qian; Teppei J. Yasunari; Sarah J. Doherty; Mark G. Flanner; William K. M. Lau; Jing Ming; Hailong Wang; Mo Wang; Stephen G. Warren; Rudong Zhang (Advances in Atmospheric Sciences, 2015)

Ecological mechanisms underpinning climate adaptation services - Sandra Lavorel; Matthew J. Colloff; Sue Mcintyre; Michael D. Doherty; Helen T. Murphy; Daniel J. Metcalfe; Michael Dunlop; Richard J. Williams; Russell M. Wise; Kristen J. Williams (Global Change Biology, 2015)
Ecosystem services are typically valued for their immediate material or cultural benefits to human wellbeing, supported by regulating and supporting services. Under climate change, with more frequent stresses and novel shocks, 'climate adaptation services', are defined as the benefits to people from increased social ability to respond to change, provided by the capability of ecosystems to moderate and adapt to climate change and variability. They broaden the ecosystem services framework to assist decision makers in planning for an uncertain future with new choices and options. We present a generic framework for operationalising the adaptation services concept. Four steps guide the identification of intrinsic ecological mechanisms that facilitate the maintenance and emergence of ecosystem services during periods of change, and so materialise as adaptation services. We applied this framework for four contrasted Australian ecosystems. Comparative analyses enabled by the operational framework suggest that adaptation services that emerge during trajectories of ecological change are supported by common mechanisms: vegetation structural diversity, the role of keystone species or functional groups, response diversity and landscape connectivity, which underpin the persistence of function and the reassembly of ecological communities under severe climate change and variability. Such understanding should guide ecosystem management towards adaptation planning.

Comparison of methods used to calculate typical threshold values for potentially toxic elements in soil - Rebekka McIlwaine; Siobhan F. Cox; Rory Doherty; Sherry Palmer; Ulrich Ofterdinger; Jennifer M. McKinley (Environmental Geochemistry and Health, 2014)

Hydrologic Regimes Revealed Bundles and Tradeoffs Among Six Wetland Services - James M. Doherty; Jeffrey F. Miller; Stephanie G. Prellwitz; Anita M. Thompson; Steven P. Loheide; Joy B. Zedler (Ecosystems, 2014)

Impact of peatland drainage and restoration on esker groundwater resources: modeling future scenarios for management - Pekka M. Rossi; Pertti Ala-aho; John Doherty; Bjørn Kløve (Hydrogeology Journal, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Attenuated effects of experimenter-administered heroin in adolescent vs. adult male rats: physical withdrawal and locomotor sensitization - James M. Doherty; Kyle J. Frantz (Psychopharmacology, 2013)

Strategies for the profiling, characterisation and detailed structural analysis of N-linked oligosaccharides - Tharmala Tharmalingam; Barbara Adamczyk; Margaret A. Doherty; Louise Royle; Pauline M. Rudd (Glycoconjugate Journal, 2013)

Breast-feeding and risk of epithelial ovarian cancer - S. J. Jordan; K. L. Cushing-Haugen; K. G. Wicklund; J. A. Doherty; M. A. Rossing (Cancer Causes & Control, 2012)

Heroin self-administration and reinstatement of heroin-seeking in adolescent vs. adult male rats - James M. Doherty; Kyle J. Frantz (Psychopharmacology, 2012)

Functional characterisation of the bovine neuropeptide Y gene promoter and evaluation of the transcriptional activities of promoter haplotypes - Tanweer Alam; Bojlul Bahar; Sinéad M. Waters; Mark McGee; John V. O’Doherty; Torres Sweeney (Molecular Biology Reports, 2012)

Population structure and genetic diversity of greater sage-grouse (Centrocercus urophasianus) in fragmented landscapes at the northern edge of their range - Krista L. Bush; Christopher K. Dyte; Brendan J. Moynahan; Cameron L. Aldridge; Heather S. Sauls; Angela M. Battazzo; Brett L. Walker; Kevin E. Doherty; Jason Tack; John Carlson; Dale Eslinger; Joel Nicholson; et al. (Conservation Genetics, 2011)

Chromosome 15q24-25.1 variants, diet, and lung cancer susceptibility in cigarette smokers - Lori C. Sakoda; Melissa M. Loomis; Jennifer A. Doherty; Marian L. Neuhouser; Matt J. Barnett; Mark D. Thornquist; Noel S. Weiss; Gary E. Goodman; Chu Chen (Cancer Causes & Control, 2011)

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Iron intake and markers of iron status and risk of Barrett’s esophagus and esophageal adenocarcinoma - Mark G. O’Doherty; Christian C. Abnet; Liam J. Murray; Jayne V. Woodside; Lesley A. Anderson; John D. Brockman; Marie M. Cantwell (Cancer Causes & Control, 2010)

Hypothesis testing of buoyant plume migration using a highly parameterized variable-density groundwater model at a site in Florida, USA - Alyssa M. Dausman; John Doherty; Christian D. Langevin; Joann Dixon (Hydrogeology Journal, 2010)

Implications of future climate and atmospheric CO 2 content for regional biogeochemistry, biogeography and ecosystem services across East Africa - RUTH M. DOHERTY; STEPHEN SITCH; BENJAMIN SMITH; SIMON L. LEWIS; PHILIP K. THORNTON (Global Change Biology, 2010)
We model future changes in land biogeochemistry and biogeography across East Africa. East Africa is one of few tropical regions where general circulation model (GCM) future climate projections exhibit a robust response of strong future warming and general annual‐mean rainfall increases. Eighteen future climate projections from nine GCMs participating in the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment were used as input to the LPJ dynamic global vegetation model (DGVM), which predicted vegetation patterns and carbon storage in agreement with satellite observations and forest inventory data under the present‐day climate. All simulations showed future increases in tropical woody vegetation over the region at the expense of grasslands. Regional increases in net primary productivity (NPP) (18–36%) and total carbon storage (3–13%) by 2080–2099 compared with the present‐day were common to all simulations. Despite decreases in soil carbon after 2050, seven out of nine simulations continued to show an annual net land carbon sink in the final decades of the 21st century because vegetation biomass continued to increase. The seasonal cycles of rainfall and soil moisture show future increases in wet season rainfall across the GCMs with generally little change in dry season rainfall. Based on the simulated present‐day climate and its future trends, the GCMs can be grouped into four broad categories. Overall, our model results suggest that East Africa, a populous and economically poor region, is likely to experience some ecosystem service benefits through increased precipitation, river runoff and fresh water availability. Resulting enhancements in NPP may lead to improved crop yields in some areas. Our results stand in partial contradiction to other studies that suggest possible negative consequences for agriculture, biodiversity and other ecosystem services caused by temperature increases.

Maximizing resources to study an uncommon cancer: E2C2—Epidemiology of Endometrial Cancer Consortium - Sara H. Olson; Chu Chen; Immaculata De Vivo; Jennifer A. Doherty; Virginia Hartmuller; Pamela L. Horn-Ross; James V. Lacey; Shannon M. Lynch; Leah Sansbury; V. Wendy Setiawan; Leo J. Schouten; Xiao Ou Shu (Cancer Causes & Control, 2009)

Postglacial vegetation and climate dynamics in the Seymour‐Belize Inlet Complex, central coastal British Columbia, Canada: palynological evidence from Tiny Lake - Jennifer M. Galloway; Christine T. Doherty; R. Timothy Patterson; Helen M. Roe (Journal of Quaternary Science, 2009)
A pollen‐based study from Tiny Lake in the Seymour‐Belize Inlet Complex of central coastal British Columbia, Canada, permits an evaluation of the dynamic response of coastal temperate rainforests to postglacial climate change. Open Pinus parklands grew at the site during the early Lateglacial when the climate was cool and dry, but more humid conditions in the later phases of the Lateglacial permitted mesophytic conifers to colonise the region. Early Holocene conditions were warmer than present and a successional mosaic of Tsuga heterophylla and Alnus occurred at Tiny Lake. Climate cooling and moistening at 8740 ± 70 14 C a BP initiated the development of closed, late successional T. heterophylla –Cupressaceae forests, which achieved modern character after 6860 ± 50 14 C a BP, when a temperate and very wet climate became established. The onset of early Holocene climate cooling and moistening at Tiny Lake may have preceded change at more southern locations, including within the Seymour‐Belize Inlet Complex, on a meso‐ to synoptic scale. This would suggest that an early Holocene intensification of the Aleutian Low pressure system was an important influence on forest dynamics in the Seymour‐Belize Inlet Complex and that the study region was located near the southern extent of immediate influence of this semi‐permanent air mass. Copyright © 2008 John Wiley & Sons, Ltd.

Long-term effects of hydropower installations and associated river regulation on River Shannon eel populations: mitigation and management - T. K. McCarthy; P. Frankiewicz; P. Cullen; M. Blaszkowski; W. O’Connor; D. Doherty (Hydrobiologia, 2008)

Radiative forcing from surface NO x emissions: spatial and seasonal variations - R. G. Derwent; D. S. Stevenson; R. M. Doherty; W. J. Collins; M. G. Sanderson; C. E. Johnson (Climatic Change, 2008)

ABOVEGROUND AND BELOWGROUND EFFECTS OF SINGLE‐TREE REMOVALS IN NEW ZEALAND RAIN FOREST - David A. Wardle; Susan K. Wiser; Robert B. Allen; James E. Doherty; Karen I. Bonner; Wendy M. Williamson (Ecology, 2008)
There has been considerable recent interest in how human‐induced species loss affects community and ecosystem properties. These effects are particularly apparent when a commercially valuable species is harvested from an ecosystem, such as occurs through single‐tree harvesting or selective logging of desired timber species in natural forests. In New Zealand mixed‐species rain forests, single‐tree harvesting of the emergent gymnosperm Dacrydium cupressinum, or rimu, has been widespread. This harvesting has been contentious in part because of possible ecological impacts of Dacrydium removal on the remainder of the forest, but many of these effects remain unexplored. We identified an area where an unintended 40‐year “removal experiment” had been set up that involved selective extraction of individual Dacrydium trees. We measured aboveground and belowground variables at set distances from both individual live trees and stumps of trees harvested 40 years ago. Live trees had effects both above and below ground by affecting diversity and cover of several components of the vegetation (usually negatively), promoting soil C sequestration, enhancing ratios of soil C:P and N:P, and affecting community structure of soil microflora. These effects extended to 8 m from the tree base and were likely caused by poor‐quality litter and humus produced by the trees. Measurements for the stumps revealed strong legacy effects of prior presence of trees on some properties (e.g., cover by understory herbs and ferns, soil C sequestration, soil C:P and N:P ratios), but not others (e.g., soil fungal biomass, soil N concentration). These results suggest that the legacy of prior presence of Dacrydium may remain for several decades or centuries, and certainly well over 40 years. They also demonstrate that, while large Dacrydium individuals (and their removal) may have important effects in their immediate proximity, within a forest, these effects should only be important in localized patches containing high densities of large trees. Finally, this study emphasizes that deliberate extraction of a particular tree species from a forest can exert influences both above and below ground if the removed species has a different functional role than that of the other plant species present.

Multi-proxy evidence of postglacial climate and environmental change at Two Frog Lake, central mainland coast of British Columbia, Canada - Jennifer M. Galloway; R. Timothy Patterson; Christine T. Doherty; Helen M. Roe (Journal of Paleolimnology, 2007)

Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Angela M. Murphy; David E. MacHugh; Stephen D.E. Park; Erik Scraggs; Chris S. Haley; David J. Lynn; Maurice P. Boland; Michael L. Doherty (Mammalian Genome, 2007)

Sequence of RNA-dependent RNA Polymerase Genes Provides Evidence for Three More Distinct Mitoviruses in Ophiostoma Novo-ulmi Isolate Ld - Michelle Doherty; Robert H. A. Coutts; Clive M. Brasier; Kenneth W. Buck (Virus Genes, 2006)

Uptake and Persistence of the Vertebrate Pesticide, Sodium Monofluoroacetate (Compound 1080), in Plants of Cultural Importance - Shaun C. Ogilvie; James M. Ataria; James Waiwai; James E. Doherty; Michelle Lambert; Neuton Lambert; David King (Ecotoxicology, 2006)

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

Matrix Gla protein and osteopontin genetic associations with coronary artery calcification and bone density: the CARDIA study - Brent C. Taylor; Pamela J. Schreiner; Terence M. Doherty; Myriam Fornage; J. Jeffrey Carr; Steve Sidney (Human Genetics, 2005)

AGAGE Observations of Methyl Bromide and Methyl Chloride at Mace Head, Ireland, and Cape Grim, Tasmania, 1998–2001 - P. G. Simmonds; R. G. Derwent; A. J. Manning; P. J. Fraser; P. B. Krummel; S. O'Doherty; R. G. Prinn; D. M. Cunnold; B. R. Miller; H. J. Wang; D. B. Ryall; L. W. Porter; et al. (Journal of Atmospheric Chemistry, 2004)

Microcell-mediated chromosome transfer (MMCT): small cells with huge potential - Aideen M. O. Doherty; Elizabeth M. C. Fisher (Mammalian Genome, 2003)

Spatial Scale Effects of Climate Scenarios on Simulated Cotton Production in the Southeastern U.S.A. - Ruth M. Doherty; Linda O. Mearns; K. Raja Reddy; Mary W. Downton; Larry McDaniel (Climatic Change, 2003)

Low frequency of the "plateau phenomenon" during maximal exercise in elite British athletes - M. Doherty; L. Nobbs; T. D. Noakes (European Journal of Applied Physiology, 2003)

Toxicity Assessment of a Former Manufactured Gas Plant - A. S. Ferguson; R. Doherty; M. J. Larkin; R. M. Kalin; V. Irvine; U. S. Ofterdinger (Bulletin of Environmental Contamination and Toxicology, 2003)

Regional Sources of Methyl Chloride, Chloroform and Dichloromethane Identified from AGAGE Observations at Cape Grim, Tasmania, 1998–2000 - M. L. Cox; G. A. Sturrock; P. J. Fraser; S. T. Siems; P. B. Krummel; S. O'Doherty (Journal of Atmospheric Chemistry, 2003)

Second primary tumors in patients with upper aerodigestive tract cancers: joint effects of smoking and alcohol (United States) - Kim-Anh Do; Marcella M. Johnson; Dorota A. Doherty; J. Jack Lee; Xi Feng Wu; Qiong Dong; Waun K. Hong; Fadlo R. Khuri; Karen K. Fu; Margaret R. Spitz (Cancer Causes & Control, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Diel drift behaviour of fish eggs and larvae, in particular barbel, Barbus barbus (L.), in an English chalk stream - G. H. COPP; H. FAULKNER; S. DOHERTY; M. S. WATKINS; J. MAJECKI (Fisheries Management and Ecology, 2002)
To estimate the potential loss of fish larvae to downstream stretches, the downstream drift behaviour of fish eggs and larvae, in particular barbel, Barbus barbus (L.), was examined in the River Lee, a small, nutrient‐rich chalk stream in England, using drift nets over nine consecutive 24‐h periods in June 1993 at one location and over ten 24‐h periods, once a week for 10 weeks from May to July 1995 at a location slightly more upstream. The density of drifting fish larvae was not correlated with river discharge in 1993 or 1995. A clear diel pattern was found in the drift of fish eggs and larvae, with barbel being a predominant species. Almost all fish larvae drifted at night both in 1993 and 1995, but the drift of eggs in 1995 occurred regardless of luminosity, although most eggs drifted during the day and at dawn. The highest densities of drifting fish larvae (in particular barbel) were found in the nets set in the highest water velocities, with the opposite pattern observed for fish eggs, suggesting either active response to the water current or shape‐related differences in the drift behaviour of passive particles.

Dual X-ray absorptiometry detects disease- and treatment-related alterations of bone density in prostate cancer patients - Gillian L. Smith; Alan P. Doherty; Linda M. Banks; Jane Dutton; Iain W. Hanham; Timothy J. Christmas; Richard J. Epstein (Clinical & Experimental Metastasis, 2000)

Eye on the Ionosphere: The Correlation between Solar 10.7 cm Radio Flux and Ionospheric Range Delay - Patricia H. Doherty; John A. Klobuchar; Joseph M. Kunches (GPS Solutions, 2000)

Route-Dependent Metabolism of Morphine in the Vascularly Perfused Rat Small Intestine Preparation - Margaret M. Doherty; K. Sandy Pang (Pharmaceutical Research, 2000)

Hydroxyl Radical Concentrations Estimated from Measurements of Trichloroethylene during the EASE/ACSOE Campaign at Mace Head, Ireland during July 1996 - R. G. Derwent; N. Carslaw; P. G. Simmonds; M. Bassford; S. O'Doherty; D. B. Ryall; M. J. Pilling; A. C. Lewis; J. B. McQuaid (Journal of Atmospheric Chemistry, 1999)

A population of wheat and tritordeum transformants showing a high degree of marker gene stability and heritability - M. E. Cannell; A. Doherty; P. A. Lazzeri; P. Barcelo (Theoretical and Applied Genetics, 1999)

On the Use of Surrogate Species in Conservation Biology - T. M. Caro; Gillian O'Doherty (Conservation Biology, 1999)
Conservation biologists have used surrogate species as a shortcut to monitor or solve conservation problems. Indicator species have been used to assess the magnitude of anthropogenic disturbance, to monitor population trends in other species, and to locate areas of high regional biodiversity. Umbrella species have been used to delineate the type of habitat or size of area for protection, and flagship species have been employed to attract public attention. Unfortunately, there has been considerable confusion over these terms, and several have been applied loosely and interchangeably. We attempt to provide some clarification and guidelines for the application of these different terms. For each type of surrogate, we briefly describe the way it has been used in conservation biology and then examine the criteria that managers and researchers use in selecting appropriate surrogate species. By juxtaposing these concepts, it becomes clear that both the goals and selection criteria of different surrogate classes differ substantially, indicating that they should not be conflated. This can be facilitated by first outlining the goals of a conservation study, explicitly stating the criteria involved in selecting a surrogate species, identifying a species according to these criteria, and then performing a pilot study to check whether the choice of species was appropriate before addressing the conservation problem itself. Surrogate species need to be used with greater care if they are to remain useful in conservation biology.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

A gridded reconstruction of land and ocean precipitation for the extended tropics from 1974 to 1994 - Ruth M. Doherty; Mike Hulme; Colin G. Jones (International Journal of Climatology, 1999)

Isolation of salmon pancreas disease virus (SPDV) from farmed Atlantic salmon, Salmo salar L., in Scotland - H. M. Rowley; C. E. Doherty; M. F. McLoughlin; M. D. Welsh (Journal of Fish Diseases, 1998)
A toga‐like virus was recently isolated in the present authors' laboratory from Atlantic salmon during an outbreak of PD in Ireland (Nelson, McLoughlin, Rowley, Platten & McCormick 1995). When inoculated into Atlantic salmon post‐smolts, this virus, known as salmon pancreas disease virus (SPDV), caused pathological changes in the pancreas, heart and skeletal muscle which were indistinguishable from those observed in natural outbreaks of PD (McLoughlin, Nelson, Rowley, Cox & Grant 1996). In 1996 a serological survey was carried out to determine the presence and distribution of antibodies to SPDV in Irish, Scottish and Norwegian farm‐reared Atlantic salmon (McLoughlin, Rowley & Doherty 1998). The results of this survey indicated that SPDV is present in the major European salmon‐producing countries. The present paper describes the first isolation of SPDV from farm‐reared, PD‐affected Atlantic salmon in Scotland.

Characterisation of the Glass Transition of an Amorphous Drug Using Modulated DSC - Paul G. Royall; Duncan Q. M. Craig; Christopher Doherty (Pharmaceutical Research, 1998)

Objectives and background to the 1994 Franco-Australian expedition to Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - R. Galzin; S. Planes; M. Adjeroud; C. Chauvet; P. J. Doherty; J. Poupin (Coral Reefs, 1998)

Replenishment of fish populations in the enclosed lagoon of Taiaro Atoll: (Tuamotu Archipelago, French Polynesia) evidence from eggs and larvae - J. M. Leis; T. Trnski; P. J. Doherty; V. Dufour (Coral Reefs, 1998)

Microhabitat use by 0+ and older fishes in a small English chalk stream - M. S. Watkins; S. Doherty; G. H. Copp (Journal of Fish Biology, 1997)
The microhabitat use of two size/age classes of fish (0 +, ≥1+) in the River Lee, based on measurements of 14 environmental variables, was studied using point abundance sampling by electrofishing over the summer and autumn of 1995. Microhabitat use by all cyprinid species (barbel Barbus barbus, minnow Phoxinus phoxinus , chub Leuciscus cephalus and gudgeon Gobio gobio ) differed between 0+ and older (≥1+) with lentic, shallow, littoral environments being important for 0+ fishes, whereas deeper, faster areas in mid‐channel were important for ≥ 1 + fishes. There was more overlap in microhabitat use by 0+ juvenile cyprinids in the River Lee than in larger systems such as the River Danube (Slovakia/Hungary) and River Great Ouse (U.K.).